Balance in academic leadership: Voices of women from Turkey and the United States of America (US) - Özge Hacifazlioglu (Perspectives in Education, 2010)
This comparative study examines the experiences of women leaders in Turkey and the US. It argues that the theme of ‘balance in leadership’ appeared to be the most influential driving force in women leaders’ stories. It further shows that balance in leadership is associated with balance in two areas: balancing private and professional life, and balance in research, teaching and leadership. The analysis is based on qualitative interviews with nineteen women leaders working at four-year public and private (foundation) universities in Turkey and the US. It is hoped that aspiring leaders can learn from these women’s experiences.